2012
DOI: 10.5530/pj.2012.32.12
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and α-glucosidase inhibitory activities of Murraya koenigii leaf extracts

Abstract: Medicinal plants are source for a wide variety of natural antioxidants. Dietary antioxidant consumption may be an important approach for inhibiting or delaying the oxidation of susceptible cellular substrates and thus is relevant to disease prevention in many paradigms. Murraya koenigii is one of the important medicinal herb which is used as a food ingredient across India. In this study, we demonstrated the reducing power, total antioxidant potential, radical scavenging capabilities and α-glycosidase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It has also been shown that Murrya koenigii exerts insulin sensitizing and antioxidant activities, besides its α-glucosimidase inhibitory activity that can aid in glycemic control. 76 , 77 Ocimun tenuiflorum leaves are traditionally used in diabetes in Malaysia. Investigation on the hypoglycemic effects of O. tenuiflorum extract revealed preventing of hepatic gluconeogenesis as well as activation of glucose uptake in adipose tissues and skeletal muscle.…”
Section: Herbal Remedy In Diabetesmentioning
confidence: 99%
“…It has also been shown that Murrya koenigii exerts insulin sensitizing and antioxidant activities, besides its α-glucosimidase inhibitory activity that can aid in glycemic control. 76 , 77 Ocimun tenuiflorum leaves are traditionally used in diabetes in Malaysia. Investigation on the hypoglycemic effects of O. tenuiflorum extract revealed preventing of hepatic gluconeogenesis as well as activation of glucose uptake in adipose tissues and skeletal muscle.…”
Section: Herbal Remedy In Diabetesmentioning
confidence: 99%
“…The natural products symbolize safety in contrast to the synthetic drugs, but still there is need to check their efficacy with systematic studies. Therefore, the need for new therapeutic options has prompted many researchers to evaluate the efficacy of compounds found in natural products [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…M. koenigii was tested for the α-glucosidase inhibitory property and was found to inhibit α glycosidase. Alpha-glucosidase inhibitors are widely used in the treatment of patients with type 2 diabetes [113]. A study reported that an ethanolic extract of M. koenigii showed a significant reduction in blood glucose levels, and this effect of reducing blood glucose by M. koenigii is mediated by antioxidant properties and insulin mimetic effects.…”
Section: Antidiabetic Activitymentioning
confidence: 99%